2010
DOI: 10.1593/neo.92048
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Induces Cytotoxicity through the Mitogen-Activated Protein Kinase Pathways ana Activating Transcription Factor 3

Abstract: The mechanisms underlying the proapoptotic effect of the chemotherapeutic agent, cisplatin, are largely undefined. Understanding the mechanisms regulating cisplatin cytotoxicity may uncover strategies to enhance the efficacy of this important therapeutic agent. This study evaluates the role of activating transcription factor 3 (ATF3) as a mediator of cisplatin-induced cytotoxicity. Cytotoxic doses of cisplatin and carboplatin treatments consistently induced ATF3 expression in five tumor-derived cell lines. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 39 publications
7
64
0
Order By: Relevance
“…In A549 lung carcinoma cells, targeting ATF3 with specific siRNA also attenuated the cytotoxic effects of cisplatin. Likewise, ATF3(Ϫ/Ϫ) MEFs were shown to be less sensitive to cisplatin-induced cytotoxicity compared with ATF3(ϩ/ϩ) MEFs (St Germain et al, 2010). In this present study, we first demonstrated that cisplatin could induce TS and TP expression through the activation of ERK1/2.…”
Section: Discussionsupporting
confidence: 53%
“…In A549 lung carcinoma cells, targeting ATF3 with specific siRNA also attenuated the cytotoxic effects of cisplatin. Likewise, ATF3(Ϫ/Ϫ) MEFs were shown to be less sensitive to cisplatin-induced cytotoxicity compared with ATF3(ϩ/ϩ) MEFs (St Germain et al, 2010). In this present study, we first demonstrated that cisplatin could induce TS and TP expression through the activation of ERK1/2.…”
Section: Discussionsupporting
confidence: 53%
“…Notably, it is unclear how miR-483-5p can be downregulated by cisplatin. Previous studies have demonstrated that cisplatin could induced transcriptomics responses, such as the changes in the expression of HNF4-α, SP1, c-MYC, TP53 [31] and ATF3 [32]. Moreover, alterations in gene promoter methylation have also been found by cisplatin treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of ATF3, a member of the AP-1 subfamily activating transcription factors, is quite robust relative to the levels of other oxidative stress-induced AP-1 proteins (42). We found that transcription factor binding sites for the AP-1 family presenting in the regulatory element of hMSH2 were matched to ATF3 transcription factor binding sites (43)(44)(45): AP-1, Ϫ611 to Ϫ605 (5Ј-TGAATCA-3Ј) and Ϫ297 to Ϫ291 (5Ј-TGAGTAA-3Ј); ATF/cAMP-response element, Ϫ1156 to Ϫ1149 (5Ј-TGACGTCA-3Ј). Therefore, we tested if ATF3 is involved in the regulation of ectopic expression of hMSH2 during oxidative stress.…”
Section: Atf3 Acts As Executor Inducing Ectopic Expression Of Hmsh2 Rmentioning
confidence: 91%